Reduction of Taylor–Aris dispersion by lateral mixing for chromatographic applications. Issue 21 (25th September 2020) - Westerbeek, Eiko Y.; Bomer, Johan G.; Olthuis, Wouter; Eijkel, Jan C. T.; De Malsche, Wim
Abstract : We demonstrate a method to reduce Taylor–Aris dispersion by lateral mixing in a newly designed silicon AC-electroosmotic flow mixer and with this improve a reverse-phase chromatographic separation of coumarins. Abstract : Chromatographic columns are suffering from Taylor–Aris dispersion, especially for slowly diffusing molecules such as proteins. Since downscaling the channel size to reduce Taylor–Aris dispersion meets fundamental pressure limitations, new strategies are needed to further improve chromatography beyond its current limits. In this work we demonstrate a method to reduce Taylor–Aris dispersion by lateral mixing in a newly designed silicon AC-electroosmotic flow mixer. We obtained a reduction in κ aris by a factor of three in a 40 μm × 20 μm microchannel, corresponding to a plate height gain of 2 to 3 under unretained conditions at low to high Pe values. We also demonstrate an improvement of a reverse-phase chromatographic separation of coumarins.